2022
DOI: 10.1532/hsf.4525
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Occurrence of Acute Pulmonary Embolism in the ICU Ward and Related Risk Factors Predicting Its Severity

Abstract: Objective: To investigate the occurrence of acute pulmonary embolism in the intensive care unit (ICU) and analyze the related risk factors for predicting its severity. Methods: From January 2016 to December 2020, 83 patients with acute pulmonary embolism in the intensive care unit of Peking University People's Hospital were selected as the research subjects, including 34 males (40.96%) and 49 females (59.04%), with an average age of 62.06±16.83 years. The patients were divided into a high-risk group (N = 31), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a result, we were able to prevent patient selection biases, misdiagnosis, and the inappropriate demography for our study [6,11]. Lastly, our study findings identified clinical features such as APACHE II, Ctn1, NT-Pro BNP, D-dimers, and platelets that can be used to predict the severity of PE and the risk variables that affect its prognosis, as well as guide clinical treatment [11,20].…”
Section: Limitationmentioning
confidence: 82%
See 1 more Smart Citation
“…As a result, we were able to prevent patient selection biases, misdiagnosis, and the inappropriate demography for our study [6,11]. Lastly, our study findings identified clinical features such as APACHE II, Ctn1, NT-Pro BNP, D-dimers, and platelets that can be used to predict the severity of PE and the risk variables that affect its prognosis, as well as guide clinical treatment [11,20].…”
Section: Limitationmentioning
confidence: 82%
“…In continuation, our study found no differences in severity APACHE II scores based on gender outcomes; overall, females registered more deaths than men but not statistically significant (Table 3). In comparison to males, most females had severe symptoms, even cardiac markers (NT-pro BNP and Ctn1), as well as D-dimers, were found to be higher in the blood, indicated the severity of PE [20] (Tables 1 and 2). We postulated PE related complications and other metabolic defects such as low pH, lactic acidosis, ventilation-related problems, and therapeutic complications.…”
Section: Discussionmentioning
confidence: 99%